The role of speech-language pathologists in adult palliative care. (2nd January 2017) - Chahda, Laura; Mathisen, Bernice A.; Carey, Lindsay B.
Abstract: Purpose : Given minimal studies describing the role and practice of speech-language pathologists (SLPs) in adult palliative care, the aim of this review was to compile a database of research literature, examine the potential research gaps and to consider material that specifically discussed the need for and/or use of procedures and protocols for SLPs working in palliative care that would support the development of SLP palliative care guidelines. Method : A scoping review was conducted utilising Arksey and O'Malley's framework with the goal of exploring any key concepts and approaches utilised by SLPs in adult palliative care, plus any literature and/or recommendations regarding SLP practice in adult palliative care settings. Result : Over 1200 articles were initially identified. Of the 1200 articles, 13 academic papers were considered relevant as they recommended, or at least suggested, the need for speech-language pathology therapy guidelines to be implemented within adult palliative care settings. Conclusion : The main focus of these articles was on ethical considerations and clinical recommendations for SLPs. Recommendations arising from this scoping review include providing goals to support current practising SLP clinicians and developing clinical guidelines to manage swallowing and/or communication needs of people receiving palliative care.